The world of fatwas, or, The shariah in action - Shourie, Arun. (New Delhi : HarperCollins Publishers, 2012)
Study of Islamic canonical decisions (Fatwas) issued in India during the last hundred years.
Includes bibliographical references and index.
Refugee Studies Unit (RSU), CPJ
Book Finder International
Keywords: Islam -- Controversial literature; Islam -- India -- Miscellanea